Effects of bidirectional resource allocation schemes for advanced long-term evolution system in heterogeneous networks. (28th September 2021) - Gatti, Ravi; Shankar, Shiva; Murthy, Keshava
The exponential growth of the wireless data services of the upcoming cellular networks exhibit challenges for guaranteeing quality of services (QoS), fairness, and desirable throughput among mobile users. Managing the resources in an advanced long term evolution system (LTE-A) is considered as one of the essential design factors for enhancing the system performance. Two-tier femto networks provide better network capacity and coverage as compared to the macro networks for multimedia applications. This paper studies the bidirectional radio resource scheduling schemes which exploit cross-tier interference. The proposed modified joint uplink/downlink user carrier scheduling (MJUCS) scheme adapts the data rates in both channels optimally through the reverse frequency allocation method. Simulation results exhibit better network coverage and enhanced throughput of mobile users with dominant mitigation of cross-layer and co-channel interference. The obtained results prove that the MJUCS algorithm can satisfy real-time applications while improving the overall system performance.